miR-33 inhibition as a novel therapeutic approach for treating muscular dystrophy - Michael A Lopez; Matthew S Alexander (EMBO Molecular Medicine)
Duchenne muscular dystrophy (DMD) is a devastating disorder caused by pathogenic variants in the dystrophin gene resulting in the absence of a functional dystrophin protein. While the primary cause of DMD is well-documented, the impact of disrupted secondary signaling pathways in dystrophic muscles and organs is still being unraveled. MicroRNAs are small, non-coding RNAs known to regulate key signaling pathways in growth, regeneration, and disease. In this issue of EMBO Molecular Medicine, Sowa and colleagues report the inhibition of a key microRNA (miR-33a/b) that when inhibited can improve muscle regeneration and mitigate dystrophic symptoms in a DMD (mdx) mouse model. miR-33a/b knockout mice showed enhanced muscle regeneration response to cardiotoxin injury and attenuated muscle fibrosis on the mdx background. miR-33a/b muscle expression blocked muscle satellite cell proliferation impaired muscle regeneration while increasing by targeting Cdk6, Fst, and Abca1 transcripts. Injection of anti-microRNA oligonucleotides (AMOs) targeting miR-33a/b improved muscle regeneration, histopathologies, and dystrophic regeneration signaling pathways. These studies demonstrate the impact of key secondary signaling pathways that may serve as new therapeutic avenues for the treatment of DMD symptoms.